In house calibration of pd detector system for field test result reliability - Raj A.; Chakrabarty C.K.; Ismail R.; Ghani B.A. (Asian Research Publishing Network, 2023)
Partial Discharge is a phenomenon that indicates cables or joints deterioration in an electrical transmission or distribution system. Mechanical damages, voids or contamination in the insulation of cables or joints may contribute to the degradation thus emission of PD is present. The electromagnetic pulses emitted may represent the condition of the insulation. Current PD detector designed using Patch Antenna with combination of FPGA and ADC is capable to pinpoint the PD source however to ensure the reproducibility between PD detectors, a calibration method has to be established. 2006-2016 Asian Research Publishing Network (ARPN).